Soil fertility status and Striga hermonthica infestation relationship due to management practices in Western Kenya - Larsson, Miriam (SLU/Dept. of Soil and Environment, 2012)
Striga hermonthica, a parasitic weed, has long been believed to be correlated with the declining soil fertility status. However scientists have recently come to question this statement since some recent studies have shown contradictive results. To investigate whether soil fertility status and infestation of Striga hermonthica were correlated and the impact of it were caused by farmer management, 120 farmers in Western Kenya, where Striga hermonthica infestation is prone, participated in this study. In three districts with two sub-locations each, farmers answered a structural questionnaire and identified two fields, one with high and one with low soil fertility. These fields later came to be the basis for this study and soil were therefore also sampled from them. Different soil variables such as: pH, ohlsen-P, texture, C, N, and seed bank of Striga hermonthica, were then analyzed. The Striga seed bank differed significantly between the districts, but there were no differences between the farms or the two fields (high and low soil fertility) on each farm. pH, C and N gave significant results for the amount of Striga seeds found in the soil. Soils with lower C:N ratio also contained fewer Striga seeds, while fields with high pH had more Striga seeds present. In Nyabeda, one of the sub-locations, trials were installed on the identified fields at 11 farms to measure actual Striga emergence in the field. Local and IR-maize were planted, both with and without fertilization. Variety was significant for both Striga emergence count and maize yield. Field status was also significant for Striga emergence. Fertilisation played no significant role in Striga emergence nor did it increase the yield. The local maize variety gave significantly higher yields than the IR-maize did. Furthermore IR-maize resulted in significantly higher emergence of Striga. Striga infestation seems to be correlated with soil fertility status, though the impact of farmer management has not been fully investigated due to the limited amount of time and data available. Further studies are needed to understand the impact of farmer management practices on Striga infestation and soil fertility.